2016
DOI: 10.1167/iovs.15-18571
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association Analysis of Drusen Progression

Abstract: PurposeAge-related macular degeneration is a common form of vision loss affecting older adults. The etiology of AMD is multifactorial and is influenced by environmental and genetic risk factors. In this study, we examine how 19 common risk variants contribute to drusen progression, a hallmark of AMD pathogenesis.MethodsExome chip data was made available through the International AMD Genomics Consortium (IAMDGC). Drusen quantification was carried out with color fundus photographs using an automated drusen detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Multiple studies have also shown that AMD-associated genetic variants are associated with disease progression, but in most studies only a subset of AMD-associated variants were used 1319 . In addition, the total number of AMD-associated variants is also known to be associated with the clinical disease stage, which was also confirmed in our study where the GRS was associated with the drusen coverage 16,24 . According to a recent prospective cohort, genetic variants only provide a limited additional predicting power when the clinical grading stage at baseline is included as predictor 15 .…”
Section: Discussionsupporting
confidence: 89%
“…Multiple studies have also shown that AMD-associated genetic variants are associated with disease progression, but in most studies only a subset of AMD-associated variants were used 1319 . In addition, the total number of AMD-associated variants is also known to be associated with the clinical disease stage, which was also confirmed in our study where the GRS was associated with the drusen coverage 16,24 . According to a recent prospective cohort, genetic variants only provide a limited additional predicting power when the clinical grading stage at baseline is included as predictor 15 .…”
Section: Discussionsupporting
confidence: 89%
“… 20 A longitudinal analysis of a small subgroup of the AREDS sample ( N = 75) did not find an association between a genetic score, including 19 common risk variants, and progression of drusen based on color photos assessed with an automated algorithm, possibly owing to low power. 29 We have previously shown that carriers of the rare variant CFH R1210C have a higher drusen burden in the macular and extra-macular locations, 26 , 30 but no previous studies have explored the impact of this high impact genetic variant or the high-risk rare C3 variant 31 on drusen size progression. Both of these rare variants were shown to be associated with drusen growth in this prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…The patients who have intermediate drusen but at least one drusen with >125 micron were considered as AREDS 3. Patients who appeared with wet and GA phenotypes were included in ADRES 4 and AREDS 5 [Hoffman et al, ].…”
Section: Methodsmentioning
confidence: 99%